Proteomic characterization of Mycobacterium tuberculosis reveals potential targets of bostrycin - Yuan, Peibo; He, Lei; Chen, Dongni; Sun, Yunhao; Ge, Zhenhuang; Shen, Dong; Lu, Yongjun (Journal of proteomics, 2020)
Tuberculosis (TB) is caused by bacterial pathogen Mycobacterium tuberculosis (Mtb) and remains a major health problem worldwide. The increasing prevalence of drug-resistant Mtb strains and the extended duration of anti-TB regimens have created an urgent need for new anti-tuberculosis antibiotics with novel targets or inhibitory strategies. Anthracenedione compound bostrycin has been shown to inhibit the growth of Mtb in vitro and inhibit the activity of the effector protein tyrosine phosphatase (MptpB) secreted by Mtb. In this study, we characterized the proteomic profile of the Mtb strain H37Ra exposed to 1 mg/L and 25 mg/L of bostrycin for 24 h. Bioinformatic analysis of the differential abundant proteins indicated that bostrycin treatment may induce oxidative stress and interfere with essential processes such as synthesis of NAD(+) and the tricarboxylic acid cycle in mycobacteria. Then, the molecular docking of bostrycin and 15 candidates of targeted proteins showed that Rv3684 and Rv1908c got higher scores compared to MptpB, suggesting the direct interaction of bostrycin and these two proteins. Further docking of potential targeted proteins with the functional group-removal derivatives of bostrycin revealed possible key functional groups of bostrycin and provides direction for the modification of bostrycin in future. It is a challenging work to determine the potential target(s) of an antibiotic accurately and quickly. In this study, we conducted a proteomic analysis of Mtb responding to the treatment of bostrycin, and provided insight into the inhibiting mechanism of this anti-Mtb compound. The proper interaction of bostrycin and targeted proteins, as well as the interacting residues of targets, and functional groups of bostrycin were also identified within the docking surface, providing a direction for further modification of bostrycin. Our study also suggests a reference for the interaction analysis between mycobacteria and antibiotics, and provides potential targets information for other active anthraquinones. [Display omitted] •Bostrycin may induce oxidative stress and interfere with the synthesis of NAD(+) and the glyoxylate cycle in Mycobacteria.•Molecular docking suggests that Rv3684 and Rv1908c may directly interact with bostrycin.•Docking of the functional group-removal derivatives of bostrycin provides direction for the modification of bostrycin.